DAMPAK REAKTIVASI STASIUN WANARAJA TERHADAP KINERJA SIMPANG JALAN CIKOLE DAN JALAN RAYA WANARAJA DI KABUPATEN GARUT - Iscahyono, Achmad Fauzan; Khairullah, Rafi Arqam; Putri, Siti Calulla (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2026)
The reactivation of Wanaraja Railway Station was carried out in March 2022 after 39 years of dormancy since 1983. With the reactivation of Wanaraja Railway Station, this is estimated to affect the intersection performance at the intersection of Cikole Street and Wanaraja Highway where the instersection is the road most often passed to get to the station. This purpose of this research is to identify the impact of reactivation of Wanaraja Railway Station on the intersectioin performance of Cikole Street and Wanaraja Highway by calculating the degree of saturation, delay, and queuing opportunities. This research uses a quantitative descriptive approach and intersection performance analytical method refers to Indonesia Highway Capacity Manual (PKJI) 2014. The results of the analysis show that the performance of the intersection of Cikole Street and Wanaraja Highway has increased that is on degree of saturation value from 0.49 to 0.74. The increase also occurs in the value of intersection delays and queue opportunities. This is because no substantial impact has been observed from the reactivation of Wanaraja Railway Station on the performance of the intersection of Cikole Street and Wanaraja Highway. Abstrak Reaktivasi Stasiun Wanaraja dilakukan pada bulan Maret 2022 setelah 39 tahun lamanya tertidur sejak tahun 1983. Reaktivasi Stasiun Wanaraja diperkirakan akan memengaruhi kinerja simpang di persimpangan Jalan Cikole dan Jalan Raya Wanaraja di mana persimpangan tersebut merupakan jalan yang paling sering dilewati untuk menuju stasiun tersebut. Penelitian ini bertujuan untuk mengidentifikasi dampak reaktivasi Stasiun Wanaraja terhadap kinerja simpang Jalan Cikole dan Jalan Raya Wanaraja dengan memperhitungan derajat kejenuhan, tundaan, serta peluang antrian. Penelitian ini dilakukan dengan menggunakan pendekatan deskriptif kuantitatif serta metode analisis kinerja lalu lintas simpang mengacu kepada Pedoman Kapasitas Jalan Indonesia (PKJI) tahun 2014. Hasil analisis menunjukkan bahwa kinerja simpang Jalan Cikole dan Jalan Raya Wanaraja mengalami peningkatan yaitu pada nilai derajat kejenuhan dari 0,49 menjadi 0,74. Peningkatan juga terjadi pada nilai tundaan simpang dan peluang antrian. Hal tersebut dikarenakan belum ada dampak yang signifikan dari reaktivasi Stasiun Wanaraja terhadap kinerja simpang Jalan Cikole dan Jalan Raya Wanaraja.